2016
DOI: 10.1074/jbc.m115.688812
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-activated Receptor-γ Coactivator 1-α (PGC1α) Protects against Experimental Murine Colitis

Abstract: Peroxisome proliferator-activated receptor-␥ coactivator 1-␣ (PGC1␣) is the primary regulator of mitochondrial biogenesis and was recently found to be highly expressed within the intestinal epithelium. PGC1␣ is decreased in the intestinal epithelium of patients with inflammatory bowel disease, but its role in pathogenesis is uncertain. We now hypothesize that PGC1␣ protects against the development of colitis and helps to maintain the integrity of the intestinal barrier. We selectively deleted PGC1␣ from the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 72 publications
6
91
0
Order By: Relevance
“…As a regulator of mitochondrial biogenesis and function, PGC-1 α plays a remarkable role in resistance to oxidative stress and mitochondrial integrity [47, 48]. There are several studies demonstrating that SIRT1 can enhance PGC-1 α activation and make it act as a substrate of deacetylation [28, 49]. In the present study, we also detected PGC-1 α levels, and its expression was dependent on the concentration of the APN peptide treatments.…”
Section: Discussionsupporting
confidence: 70%
“…As a regulator of mitochondrial biogenesis and function, PGC-1 α plays a remarkable role in resistance to oxidative stress and mitochondrial integrity [47, 48]. There are several studies demonstrating that SIRT1 can enhance PGC-1 α activation and make it act as a substrate of deacetylation [28, 49]. In the present study, we also detected PGC-1 α levels, and its expression was dependent on the concentration of the APN peptide treatments.…”
Section: Discussionsupporting
confidence: 70%
“…These results suggested that SIRT1 influences the expression of its target PGC‐1α. Indeed, several previous studies have demonstrated that SIRT1 can enhance PGC‐1α activation and make it act as a substrate of deacetylation …”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria also influence the activities of intestinal functional effector cells, such as immune cells, epithelial cells and enterochromaffin cells (Cunningham et al, 2016). These same cells, on the other hand, are under the influence of the gut microbiota, whose contributing role in mitochondria functions is becoming evident.…”
Section: Introductionmentioning
confidence: 99%